2007
DOI: 10.2967/jnumed.107.039487
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation and Small-Animal PET/CT of a Prostate Cancer Mouse Model Using 64Cu Bombesin Analogs: Side-by-Side Comparison of the CB-TE2A and DOTA Chelation Systems

Abstract: The BB2 receptor subtype, of the bombesin family of receptors, has been shown to be highly overexpressed in a variety of human tumors, including prostate cancer. Bombesin (BBN), a 14-amino acid peptide, has been shown to target the BB2 receptor with high affinity. 64 Cu (half-life 5 12.7 h, b 1 : 18%, E b1max 5 653 keV; b 2 : 37%, E b2max 5 578 keV) is a radioisotope that has clinical potential for application in both diagnostic imaging and radionuclide therapy. Recently, new chelation systems such as 1,4,8,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 34 publications
10
128
1
2
Order By: Relevance
“…(Fig. 4) for [ 64 Cu-DOTA-8-Aoc-BBN(7-14)NH 2 ] in PC-3 tumor-bearing mice were unremarkable in tumor tissue, with significant collateral abdominal accumulation presumably caused by free 64 Cu radionuclide (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fig. 4) for [ 64 Cu-DOTA-8-Aoc-BBN(7-14)NH 2 ] in PC-3 tumor-bearing mice were unremarkable in tumor tissue, with significant collateral abdominal accumulation presumably caused by free 64 Cu radionuclide (38).…”
Section: Discussionmentioning
confidence: 99%
“…They have reported the synthesis of [ 64 Cu-DOTA-8-Aoc-BBN(7-14)NH 2 ] and subsequent animal studies in PC-3 tumor-bearing SCID mouse models (38). [ 64 Cu-DOTA-8-Aoc-BBN(7-14)NH 2 ] conjugate showed very high uptake and retention of radioactivity in liver tissue with 9.56 Ϯ 5.20%, 6.95 Ϯ 4.71%, and 7.80 Ϯ 1.51% ID per g at 1, 4, and 24 h p.i., respectively (38). Uptake in tumor tissue at 1 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the development of labeled Bn analogues for imaging or targeted cytotoxicity is a very active area of investigation at present. Numerous radiolabeled [ 111 Indium, 68 Gallium, 177 Lutetium, 64 Copper, 86 Yttrium, 18 F, 99m Tc] GRP analogues with enhanced stability that bind with high affinity to BB 2 -receptors are reported, as well as there ability to image various human tumors in vivo using gamma detectors or PET imaging [10,[69][70][71][72][73][74][75][76][77]. In some preliminary studies in humans, tumors were imaged in the majority of patients, and in some cases, tumors were detected using radiolabeled Bn analogues that were not seen on other commonly used imaging modalities [75,[78][79][80].…”
Section: Iiigbb Receptors-recent Advances-tumor Imaging and Receptomentioning
confidence: 99%
“…It has been shown that the GRPR is over-expressed on the surface of T-47D breast carcinoma cells while being absent from normal breast tissues (Giacchetti et al, 1990). This receptor has served as a target for a number of diagnostic and therapeutic strategies Garrison et al, 2007;Parry et al, 2007;Biddlecombe et al, 2007;Guojun et al, 2008;Zhou et al, 2003;Ma et al, 2007). T-47D xenografts in mice have been used in preclinical investigations of a variety of diagnostic modalities (Giblin et al, 2006;Aliaga et al, 2004).…”
Section: Grpr-expressing T-47d Human Bbreast Cancer Cellsmentioning
confidence: 99%
“…A majority of the work has focused on synthesis of new ligand frameworks to chelate copper in a multi-dentate fashion to prevent loss of the Cu 2+ ion under in vivo conditions. Crossbridged TETA (1,4,8,11-tetraazacyclotetradecane-1,4,8,11-tetracetic acid) derivatives, such as 4,11-bis(carboxymethyl)-1,4,8,11-tetraazabicyclo[6.6.2]hexadecane (CB-TE2A) and 1-N-(4-aminobenzyl)-3,6,10,13,16,19-hexa-aza-bicyclo-[6.6.6]eichosane-1,8-diamine (SarAr), have shown increased copper-complex stability in vivo versus the TETA and DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) chelators (Garrison et al, 2007;Di Bartolo et al, 2001 and. Additionally, derivatives of the triazacyclononane macrocycle have produced improved stability of copper complexes .…”
Section: Micropet Imaging With Copper-64-bbn Conjugatesmentioning
confidence: 99%